2021
DOI: 10.12998/wjcc.v9.i22.6201
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal manifestations of systemic sclerosis: An updated review

Abstract: Systemic sclerosis is an autoimmune disease characterized by vascular disease, fibrosis of the skin, and internal organ dysfunction. Gastrointestinal involvement is the most frequent complication of internal organs, impacting up to 90% of patients. Gastrointestinal involvement can affect any region of the gastrointestinal tract from the mouth to the anus, with a predominance of disorders being observed at the level of the upper digestive tract. The gastrointestinal involvement primarily involves the esophagus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 126 publications
0
10
0
Order By: Relevance
“…While such a direct relationship between severity of gastrointestinal involvement and mRSS has not been previously reported, the association between mRSS and gastrointestinal involvement is not new, since it has previously been observed to be directly related to abnormalities of oesophageal motility in imaging tests such as manometry and gammagraphy 42–44. Furthermore, a study performed based on the EUSTAR cohort45 showed that patients with SSc and diffuse skin involvement had gastrointestinal symptoms earlier and more frequently (p<0.05). We found that dysphagia patients had higher rates of conditions like osteoporosis, microstomia, digital ulcers and telangiectasia.…”
Section: Discussionmentioning
confidence: 94%
“…While such a direct relationship between severity of gastrointestinal involvement and mRSS has not been previously reported, the association between mRSS and gastrointestinal involvement is not new, since it has previously been observed to be directly related to abnormalities of oesophageal motility in imaging tests such as manometry and gammagraphy 42–44. Furthermore, a study performed based on the EUSTAR cohort45 showed that patients with SSc and diffuse skin involvement had gastrointestinal symptoms earlier and more frequently (p<0.05). We found that dysphagia patients had higher rates of conditions like osteoporosis, microstomia, digital ulcers and telangiectasia.…”
Section: Discussionmentioning
confidence: 94%
“…8,9 Higher correlations ('moderate') than postulated were found between the SWAP-Swe in SSc and disease interference of daily activities of gastrointestinal symptoms and overall disease severity in our study. Although gastrointestinal symptoms are a common problem in SSc, 33 appearance concerns might influence how the person experiences their disease severity and vice versa. The SWAP-Swe in SSc correlated with other PROMs but also, to some extent, with skin involvement as assessed by a physician as well as age; this highlights that appearance concerns in SSc seem to be multidimensional, as earlier reported.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic sclerosis (SSc) is a rare and highly heterogeneous immune-mediated rheumatic disorder, first described in 1753 by Carlo Curzio, but only later named as ‘sclérodermie’ in 1847 by Gintrac 1–3. Two of the main features of SSc are Raynaud’s phenomenon and skin sclerosis, but virtually any organ system can be affected 2 4.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic sclerosis (SSc) is a rare and highly heterogeneous immune-mediated rheumatic disorder, first described in 1753 by Carlo Curzio, but only later named as ‘sclérodermie’ in 1847 by Gintrac 1–3. Two of the main features of SSc are Raynaud’s phenomenon and skin sclerosis, but virtually any organ system can be affected 2 4. In the systematic literature review by Bairkdar et al, the pooled overall prevalence was 17.6 per 100 000 individuals, with a female to male ratio of almost 5:1 5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation